Prevalence and associations of symptoms of upper extremities, repetitive strain injuries (RSI) and 'RSI-like condition'. A cross sectional study of bank workers in Northeast Brazil - Rocha Dyhanne C; Olinto Maria; da S Augusto Lia G; Nácul Luis C; Lacerda Eliana M; Wanderley Danielle C (BMC, 2005)
Abstract Background The repetitive strain injury syndrome (RSI) is a worldwide occupational health problem affecting all types of economic activities. We investigated the prevalence and some risk factors for RSI and related conditions, namely 'symptoms of upper limbs' and 'RSI-like condition'. Methods We conducted a cross-sectional study with 395 bank workers in Recife, Northeast Brazil. Symptoms of upper limbs and 'RSI-like condition' were assessed by a simple questionnaire, which was used to screen probable cases of RSI. The diagnosis of RSI was confirmed by clinical examination. The associations of potential risk factors and the outcomes were assessed by multiple logistic regression analysis. Results We found prevalence rates of 56% for symptoms of the upper limbs and 30% for 'RSI-like condition'. The estimated prevalence of clinically confirmed cases of RSI was 22%. Female sex and occupation (as cashier or clerk) increased the risk of all conditions, but the associations were stronger for cases of RSI than for less specific diagnoses of 'RSI-like condition' and symptoms of upper limbs. Age was inversely related to the risk of symptoms of upper limbs but not to 'RSI-like' or RSI. Conclusion The variation in the magnitude of risk according to the outcome assessed suggests that previous studies using different definitions may not be immediately comparable. We propose the use of a simple instrument to screen cases of RSI in population based studies, which still needs to be validated in other populations. The high prevalence of RSI and related conditions in this population suggests the need for urgent interventions to tackle the problem, which could be directed to individuals at higher risk and to changes in the work organization and environment of the general population.